IFITM1 suppression blocks proliferation and invasion of aromatase inhibitor-resistant breast cancer in vivo by JAK/STAT-mediated induction of p21 - Lui, Asona J. (Cancer Lett, 2017)
Interferon induced transmembrane protein 1 (IFITM1) belongs to a family of interferon stimulated genes (ISGs) that is associated with tumor progression and DNA damage resistance, however, its role in endocrine resistance is not known. Here, we correlate IFITM1 expression with clinical stage and poor response to endocrine therapy in a tissue microarray consisting of 94 estrogen receptor (ER)-positive breast tumors. IFITM1 overexpression is confirmed in the AI-resistant MCF-7:5C cell line and not found in AI-sensitive MCF-7 cells. In this study, the orthotopic (mammary fat pad) and mouse mammary intraductal (MIND) models of breast cancer are used to assess tumor growth and invasion in vivo. Lentivirus-mediated shRNA knockdown of IFITM1 in AI-resistant MCF-7:5C cells diminished tumor growth and invasion and induced cell death, whereas, overexpression of IFITM1 in wild-type MCF-7 cells promoted estrogen-independent growth and enhanced their aggressive phenotype. Mechanistic studies indicated that loss of IFITM1 in MCF-7:5C cells markedly increased p21 transcription, expression and nuclear localization which was mediated by JAK/STAT activation. These findings suggest IFITM1 overexpression contributes to breast cancer progression and that targeting IFITM1 may be therapeutically beneficial to patients with endocrine-resistant disease.